Models of enzyme inhibition and apparent dissociation constants from kinetic analysis to study the differential inhibition of aldose reductase. (31st December 2022) - Balestri, Francesco; Cappiello, Mario; Moschini, Roberta; Mura, Umberto; Del-Corso, Antonella
Abstract: In order to explain the negative slope of K app M / k app cat versus inhibitor concentration observed in the study of epigallocatechin gallate acting as an inhibitor of aldose reductase, a kinetic analysis was performed to rationalise the phenomenon. Classical and non-classical models of complete and incomplete enzyme inhibition were devised and analysed to obtain rate equations suitable for the interpretation of experimental data. The results obtained from the different approaches were discussed in terms of the meaning of the emerging kinetic constants. A decrease of K a p p M / k app cat versus the inhibitor concentration was revealed to be a valuable indication of the occurrence of an incomplete inhibition. This indication, which is univocal in the case of an uncompetitive inhibition, may be especially useful when the residual activity resulting from inhibition is rather low.